ID: 221. Issue 1 (November 2015) - Shih, Tiffany; Daip, Jihong; Singh, Sukhwinder; Fitzgerald-Bocarsly, Patricia
<x xml:space="preserve">Abstract</x> Dendritic cells(DCs) are a heterogeneous population that regulate both innate and adaptive immunity. Human blood DCs are broadly characterized as pDC(BDCA2+), mDC1(BDCA1+), and mDC2(BDCA3+(CD141)). While much work has focused on the functional role of CD141hi mDCs, we investigated the maturation potential and functional significance of a novel BDCA3int subtype of classically-defined pDCs. Using flow cytometry, we identified four human blood DC subsets: BDCA2+/3−, BDCA2+/3int, BDCA2−/3int, and BDCA2−/3hi. Upon stimulation with TLR9 agonists CpG-A or HSV-1, the BDCA2+/3int DCs had the highest frequency of IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7scf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>+ and TNF-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7scf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>+ production, while mDC2 were non-responsive. Although CD141+ DC produce IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qwp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ</alternatives> in response to pI:pC, both pDC populations were the highest responders to HSV-1. Virus-stimulated BDCA2+/3int DCs became more activated and mature with higher expression of co-stimulatory and migratory receptors than the BDCA2+/3− cells. IRF7, the master regulator of IFN production in pDCs, was constitutively expressed by both pDC but not BDCA2-DCs. The BDCA2+/3int DCs were more potent than BDCA2+/3− cells at the preferential acquisition of cellular material from HSV-infected Raji cells. AMNIS ImageStream analysis of morphology showed no difference in circularity and size between the BDCA2+/3int and BDCA2+/3-DCs, but the mDC2 were larger and less circular than the pDC subsets. These data indicate that BDCA2+/3int DCs exhibit major classical pDC functions, but are phenotypically and functionally distinct from BDCA2−/3int and BDCA2−/3hi DCs. Together, these results describe a novel, high functioning CD141+ pDC subset and demonstrates CD141 is not unique to mDC2.